Pheromones for cotton and rice pests - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
Simple, low cost and non-polluting techniques have been developed for protecting cotton against three species of bollworm, and for protecting rice against stem-borer. Plastic strips, impregnated with highly specific sex-attractant pheromones are...